Legal Protection for Tourism Bus Business Debtors in Fiduciary Disputes with Banking and Financing Companies: Analysis of the Constitutional Court Decisions No. 18/PUU-XVII/2019 and No. 2/PUU-XIX/2021 - Dyra M. Maradhona; Ibrahim Fajri; Desty Anggie Mustika (JURNAL MAHASISWA YUSTISI, 2026)
This research analyzes the legal protection for tourism bus business debtors involved in fiduciary disputes with banks and financing companies, focusing on the implications of the Constitutional Court Decisions No. 18/PUU-XVII/2019 and No. 2/PUU-XIX/2021. The study employs normative legal research with statute and conceptual approaches, using primary legal materials such as fiduciary law, the Constitution, and court decisions. The findings show that debtor protection operates through preventive and repressive mechanisms. Preventive protection is achieved through fair contractual clauses and procedural safeguards, while repressive protection is realized through judicial review and dispute resolution. The Constitutional Court decisions transformed fiduciary execution procedures by prohibiting unilateral repossession and requiring judicial authorization if the debtor objects. For tourism bus operators, these rulings restore legal balance and operational certainty, preventing financial loss due to unilateral asset seizures. However, obstacles remain, including low awareness of the decisions and ongoing extrajudicial practices by collectors. Therefore, further regulatory elaboration and consistent enforcement are needed to ensure equitable protection within Indonesia’s financing sector.